Pathogenic mechanisms of disease in idiopathic inflammatory myopathies: autoantibodies as clues - Wu, Yuanhui; Luo, Jiao; Duan, Lihua (Frontiers in Immunology, 2024)
Idiopathic inflammatory myopathies (IIMs) encompass a spectrum of autoimmune diseases characterized by muscle inflammation and systemic involvement. This review aimed to synthesize current evidence on the clinical significance and pathogenic mechanisms underlying autoantibodies associated with IIMs. Autoantibodies targeting aminoacyl-tRNA synthetases (ARS) play a pivotal role in antisynthetase syndrome (ASS), highlighting associations with interstitial lung disease (ILD) and distinctive clinical features. Anti-Mi-2 antibodies in dermatomyositis (DM) are hallmarked by characteristic cutaneous manifestations and favorable prognostic outcomes. Conversely, anti-TIF1 antibodies are correlated with DM and a higher risk of malignancies, implicating CD8 + T cells in its pathogenesis. Anti-MDA5 antibodies signify clinically amyopathic DM (CADM) with severe ILD, linked to dysregulated neutrophil extracellular trap (NET) formation. In immune-mediated necrotizing myopathies (IMNMs), anti-SRP and anti-HMGCR antibodies induce complement-mediated myopathy, typically following statin exposure. Additionally, anti-TRIM72 antibodies emerge as potential diagnostic markers in IIMs. Anti-cN1A autoantibodies are linked to inclusion body myositis (IBM) and play a decisive role in muscle protein degradation. Meanwhile, anti-FHL1 autoantibodies are associated with severe disease manifestations and muscle damage, as established in experimental models. Anti-eIF3 autoantibodies, recently identified in polymyositis (PM) patients, are rarely detected (<1%) and associated with a favorable prognosis. Elucidating these autoantibodies is anticipated to not only assist in early diagnosis and disease stratification but also inform targeted therapeutic interventions, emphasizing the intricate interplay between autoimmunity, cellular dysfunction, and clinical outcomes in IIMs.